2020
DOI: 10.3389/fpubh.2020.00060
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Relationship Between Suicide and Unemployment in Mexico: Evidence From Linear and Non-linear Co-integration

Abstract: This study attempts to investigate if suicide is interlinked with unemployment in Mexico by making use of a recently developed Bootstrap ARDL bound test over the years of 1981-2016. To avoid omitting variable bias, we use economic growth rate as a control variable. The empirical results indicate that no co-integration among these three variables and there is a positively bidirectional causality between suicide rate and the unemployment rate. This study will showcase that the economic growth rate negatively aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…The gender distribution of cases of suicide is thus similar to that in Germany as a whole in 2020, in which 75.7% of those who completed suicide were men (Federal Health Service Germany/Statistisches . Consistent with studies reporting an association between suicides and suicidal ideation with unemployment or duration of unemployment (Breuer, 2015;Faria et al, 2020;Fountoulakis, 2020;Wang et al, 2020), the unemployment rate was 37.1% in the ITS sample whereas it was 7.6% in Hamburg overall at the time (Federal Agency of Work Germany/Bundesagentur für Arbeit, 2021).…”
Section: Discussionsupporting
confidence: 81%
“…The gender distribution of cases of suicide is thus similar to that in Germany as a whole in 2020, in which 75.7% of those who completed suicide were men (Federal Health Service Germany/Statistisches . Consistent with studies reporting an association between suicides and suicidal ideation with unemployment or duration of unemployment (Breuer, 2015;Faria et al, 2020;Fountoulakis, 2020;Wang et al, 2020), the unemployment rate was 37.1% in the ITS sample whereas it was 7.6% in Hamburg overall at the time (Federal Agency of Work Germany/Bundesagentur für Arbeit, 2021).…”
Section: Discussionsupporting
confidence: 81%
“…In 2017, a Korean study reported the risk factors affecting suicide rate in young and middle-aged adults and showed that low income and alcohol consumption played an important role 18 . According to UNICEF, because of the coronavirus induced lockdown, availability of education decreased, pushing more children into child labour [19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…Although the health-growth literature is not entirely conclusive, the preponderance of studies substantiates the positive ramifications of economic development on health, see O'Donoghue et al (25), Subramanian et al (26), Tapia Granados and Ionides (27), Renton et al (28), Morgado (29), Cole (30), amongst others. Recent studies by Wang (31), Breuer (32), and Wang et al (33) assert a synchronization of mortality with unemployment across various countries. Therefore, while economic growth is vital for health, contractions in economic growth driven by heightened economic uncertainty could bring adverse health consequences.…”
Section: Economic Growth Channelmentioning
confidence: 99%